Pengaruh Senam Lanjut Usia Terhadap Kualitas Tidur Lanjut Usia Wanita Di Boyolali - Latifah, Nadia Evariyanti; , Dwi Rosella Komalasari, S.Fis, M.Fis, Dipl.Cidesco (2017)
Background: Sleep is a basic human need. Getting old is getting a bit of sleed needed. Changes in sleep patterns will impact sleep quality in elderly. Risk factors that affect sleep quality such as physiology, phsicology and environment. PSQI (Pittburgh Sleep Quality Index) used to measure sleep disturbances in elderly. It contains 19 item quesionnaire with 7 main quetions about sleep difficulties, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbance, sleep medication usage and daytime dysfunction. Objective: To determine the effect of geriatric gymnastics on the sleep quality of women elderly. Method: The research uses the experimental analytical method with pre test - post test and control group design aims to determine the effect of geriatric gymnastics on the sleep quality of women elderly. Subject of the research was 54. PSQI was used to measure the quality of sleep. Result: Wilcoxon test was used to examine the hypothesis and the result was p=0,002 for treatment group it means there was an significant effect because p<0,005, and p=1,000 for control group means there was no significant effect because p>0,005. To find out the different influences, Mann Whitney test was used and the result is p=0,000. Conclusion: There was an effect of geriatric gymnastics on the sleep quality of women elderly.